Principios y prácticas para el manejo de nutrientes en la produccion de Hortalizas - Alejandra Sierra; Eric Simonne; Danielle Treadwell (EDIS)
HS-1102, a 20-page fact sheet by Alejandra Sierra, Eric Simonne, and Danielle Treadwell, explains 5 key principles and 3 key practices for nutrient management in vegetable production for Spanish-speaking audiences. Includes references, and several tables. Published by the UF Department of Horticultural Sciences, July 2007.